PEMETAAN POSISI ROBOT SOCCER MENGGUNAKAN GYRODOMETRY DAN TRIGONOMETRY UNTUK MEMPREDIKSI SUDUT TENDANGAN - Agus Khumaidi (Politeknik Negeri Jakarta, 2020)
The main robot that robots must have in wheeled balls is the ability to find balls, position in the goal, kick the ball and between robots with base station in the wheeled Indonesian Soccer Robot Contest (KRSBI). Wheeled type. KRSBI is one of the activities that are part of the Indonesian Robot Contest (KRI) as a venue for engineering and design competition in the field of robotics. One obstacle to the robot In the detection of the goal is still applying the Robust Algorithms method using only a camera, so that the search process is still relatively slow and kicking the ball is still often deviated from the opponent's goal. In this research, applying the Gyrodometry method in mapping the position of the robot in the field based on reading the sensor data of Rotary encoder and Gyroscope. Then the data will be sent from the microcontroller to the base station via PC and Router to be mapped. Whereas to detect the goal using Trigonometry calculation with the search of the goal based on the position of the robot's data on the Field with the opponent's goal point. The advantage of applying the Gyrodometry method in mapping the position of the robot in the field and Trigonometry calculations for goal detection can improve the efficiency of the robot to detect the goal with average speed (2.1s) and with an accuracy of 91.7%.